2013
DOI: 10.1055/s-0033-1351662
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Tracheomalacia with Aortopexy in Children in Glasgow

Abstract: There were no clinical predictors of outcome identified, but aortopexy is a safe effective procedure for children with severe tracheomalacia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Clinicians should therefore consider the potential need for anti-reflux medications in children with TBM. Children in this study also demonstrated high indices of prematurity, previous intubations, NICU/PICU admissions, OA/ TOF, cardiac abnormalities, and syndromic disease, all of which prominently feature in series containing children with moderate to severe TBM [22][23][24] .…”
Section: Summary Of Main Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Clinicians should therefore consider the potential need for anti-reflux medications in children with TBM. Children in this study also demonstrated high indices of prematurity, previous intubations, NICU/PICU admissions, OA/ TOF, cardiac abnormalities, and syndromic disease, all of which prominently feature in series containing children with moderate to severe TBM [22][23][24] .…”
Section: Summary Of Main Resultsmentioning
confidence: 56%
“…Several papers have investigated predictors of successful outcome following TBM surgery. This includes our unit's experience with 30 patients, which did not demonstrate any obvious predictors of positive post-operative outcome 23 . Others have identified varying predictors of postoperative mortality, including cardiovascular disease, pre-operative ventilation requirement, and bronchomalacia 34,35 .…”
Section: Summary Of Main Resultsmentioning
confidence: 91%